Tax progression: International and intertemporal comparisons using LIS data - Kirill Pogorelskiy; Christian Seidl; Stefan Traub (Luxembourg Income Study (LIS), 2010)
Based on the earlier work of one of the authors, this paper develops a unified methodology to compare tax progression for dominance relations under different income distributions. We address it as uniform tax progression for different income distributions and present the respective approach for both continuous and discrete cases, the latter also being employed for empirical investigations. Using dominance relations, we define tax progression under different income distributions as a class of natural extensions of uniform tax progression in terms of taxes, net incomes, and differences of first moment distribution functions. To cope with different monetary units and different supports of the income distributions involved, we utilized their transformations to population and income quantiles. Altogether, we applied six methods of comparing tax progression, three in terms of taxes and three in terms of net incomes, which we utilized for empirical analyses of comparisons of tax progression using data from the Luxembourg Income Study. This is the first paper that performs international and intertemporal comparisons of uniform tax progression with actual data.
Keywords: H23; H24; 330; income tax progression; measurement of uniform tax progression; comparisons of tax progression; tax progression with different income distributions; Einkommensteuertarif; Steuerprogression; Steuerbelastung; Steuerinzidenz; Einkommensverteilung; Vergleich; Welt; USA; Großbritannien; Deutschland